2014
DOI: 10.5267/j.msl.2014.5.002
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the effects of organizational memory and human capital on innovation and absorptive capacity

Abstract: Innovation is considered as an enabling tool for creating value and sustainable competitive advantage for organizations in dynamic environment of our times along with its ever-increasing complexities. Until innovation in developing countries needs more capital and talent, human capital (HC) is a key factor in innovative performance. People are the most important factor of exploitation of foreign knowledge; and knowledge focus in business environment is highly dependent on external information sources in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
3
0
0
Order By: Relevance
“…The results of this study show all KMPs have a significant and positive effect on ACAP, which supports the findings of (Balle et al, 2020;Bosch-Sijtsema and Henriksson, 2014;Camison and Fores, 2011;Cheuk et al, 2017;De zubielqui et al, 2016;Krstic and Petrovic, 2012;Kostopoulos et al, 2011;Mansouri et al, 2014;Moilanen et al, 2014;Su et al, 2013). Furthermore, the results strongly suggest that an increase in ACAP leads to an improvement in OP, which supports the findings of (Kostopoulos et al, 2011;Liu et al, 2013;Tsai, 2001).…”
Section: Discussion Of Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The results of this study show all KMPs have a significant and positive effect on ACAP, which supports the findings of (Balle et al, 2020;Bosch-Sijtsema and Henriksson, 2014;Camison and Fores, 2011;Cheuk et al, 2017;De zubielqui et al, 2016;Krstic and Petrovic, 2012;Kostopoulos et al, 2011;Mansouri et al, 2014;Moilanen et al, 2014;Su et al, 2013). Furthermore, the results strongly suggest that an increase in ACAP leads to an improvement in OP, which supports the findings of (Kostopoulos et al, 2011;Liu et al, 2013;Tsai, 2001).…”
Section: Discussion Of Resultssupporting
confidence: 87%
“…They allow the organization to have an "organizational memory" (OM) that is internal knowledge accumulated over time. According to Mansouri et al (2014), mechanisms of OM are supposed to acquire and to preserve the knowledge inside an organization while making it retrievable and reusable (Dzbor and Paralic, 2000). Mansouri et al (2014) results showed that OM influence ACAP positively and significantly, which confirms previous researches.…”
Section: Impact Of Kmps On Organizational Performancesupporting
confidence: 78%
See 1 more Smart Citation